In vitro Antioxidant, Antibacterial Activities and HPLC-TOF/MS Analysis of Anvillea radiata (Asteraceae) Extracts - Benslama, Abderrahim; Harrar, Abdenassar; Gül, Fatih; Demirtaş, Ibrahim (Current Nutrition & Food Science, 2019)
Background: Algeria has a particular geographical position with a wide band of very varied vegetation including the aromatic and medicinal plants. These plants are able to produce much diversified natural compounds, which can be very useful health care and treatment of diseases. Objective: This study was carried out to evaluate the antioxidant capacity and antibacterial activity of Anvillea radiata (Asteraceae) extracts, one of the medicinal plants used as food and in folk medicine in Algeria. Methods: The extraction was carried on the aerial part by methanol and water to give Met.E and Aq.E. The ABTS and DPPH free radicals-scavenging tests are used to evaluate the antioxidant activity of extracts. Moreover, the antibacterial activity was evaluated using disc diffusion method. Finally, the extracts were subject to the phytochemical analysis using the HPLC-TOF/MS equipment. Results: The Met.E showed the highest amount of total phenolic and flavonoids content (266.12 μg EAG/mg E and 50.83 μg EQ/mg E, respectively). The results of the antioxidant activity revealed that the Met.E showed a good scavenging activity against ABTS and DPPH free radical with EC50=0.067 mg/ml and EC50=0.33 mg/ml, respectively. Moreover, the A. radiata extracts present a highest antibacterial activity against M. luteus NRRL B-4375, B. subtilis NRRL NRS-744 and S. aureus ATCC 25923, with inhibition zone ranging from 18 to 23 mm to Met.E and 12-18 mm to the Aq.E. In addition, the Met.E of A. radiata showed a better MIC against S. aureus, M. luteus and B. subtilis (MIC= 6.25, 25 and 25 μg/ml, respectively). The HPLC-TOF/MS analysis of Met.E reveals the presence of two major compounds, rutin and fumaric acid, when Aq.E contains the syringic acid as a major compound. Conclusion: The data of our study reported that the Met.E extract of A. radiata had a considerable antioxidant capacity and antibacterial effect, which may be due to their richness by phenolic compounds such as rutin and fumaric acid.
Keywords: phenolic compounds